The organic chem lab survival manual a student's guide to techniques - Zubrick, James W. (Wiley, 2016)
Written for the laboratory that accompanies the sophomore/junior-level courses in Organic Chemistry, Zubrick provides students with a valuable guide to the basic techniques of the Organic Chemistry lab. The book will help students understand and practice good lab safety. It will also help students become familiar with basic instrumentation, techniques, and apparatus and help them master the latest techniques such as interpretation of infrared spectroscopy. The guide is mostly macroscale in its orientation.